Democedes of Corton and the State of Pre-Hippocratic Medicine in Ancient Greece - Papalas, Anthony J. (My University, 2008)
Laupus Library History Collections & the Department of Bioethics & Interdisciplinary Studies sponsor the History of Medicine Presentations as an educational service for the East Carolina University community. The Library hopes that the speakers and topics selected will promote a greater understanding of the historical and philosophical underpinnings of today's health care disciplines.
Keywords: MHIG; Medical History Interest Group; History, Ancient; History of Medicine; Ancient Lands; Greece